Sustainable management of transnational megaprojects - Cottafava, Dario; Torchia, Daniel; Camoletto, Stefania; Corazza, Laura (Routledge, Taylor & Francis Group ; G. Giappichelli Editore, 2024)
"This scholarly work delves into the intricate realm of megaprojects, characterized by their colossal scale, complexity, and societal impact. It offers a comprehensive analysis of the multifaceted challenges that confront these ventures, spanning stakeholder conflicts, environmental, social, and economic sustainability concerns, and the unique characteristics of each project. The book presents a structured exploration, spanning seven chapters, which combine theoretical frameworks and empirical insights. It elucidates the fundamental components essential for sustainable megaproject management, emphasizing the significance of social responsibility. It establishes a crucial link between critical infrastructure and sustainable development, unraveling paradoxes. Furthermore, it scrutinizes the state of research in the field, highlights critical areas in accounting studies within the context of megaprojects, and identifies emerging research trends. The book concludes by examining a specific case study of a transnational megaproject. In sum, this scientific endeavor aims to address the pressing challenges of sustainable megaproject management, providing a holistic and systemic approach that accounts for all dimensions of sustainability and inclusive stakeholder engagement. It contributes to the evolving discourse on the governance and management of transnational megaprojects in a dynamically changing world"-- Provided by publisher.
Keywords: Project management.; Sustainable development.; elektronické knihy; electronic books